EVOLUÇÃO DA MORFOLOGIA ALAR EM TRÊS FAMÍLIAS DE MORCEGOS NEOTROPICAIS - Santos, Fernanda Almeida (2018)
Bats are the only mammals that flying, and their wings shape may restrict or allow the exploration of environments and performing different ways of foraging modes. This shape variation may have been conserved within lineages or may be result of homoplasy. In this way the objective of this work was to analyze what most influenced the wing shape of the bats along the evolution, whether it was a morphological conservation in evolutionary history of the clades or a convergent selective process generating homoplasy. Were used photos of 121 individuals belonging to 22 species within 3 neotropical bat families (Vespertilionidae, Molossidae and Phyllostomidae). Geometric morphometry was used to extract information of wing shape from 11 anatomical landmarks were inserted in the images of left wings of each individual. Effects of position, size and orientation of the coordinates were eliminated through a Generalized Procrustes Analysis (GPA). A variance and covariance matrix was extracted from means for each species and then subjected to a Principal Component Analysis (PCA). A Chiroptera phylogeny was pruned to contain only species analyzed. Wing form phylogenetic history was then visualized projecting the phylogeny in the morphospace defined by the first two main components. Reconstruction of ancestral characters was performed using squaredchange parsimony method and phylogenetic signal was tested by permutation for shape and size data. Ordinary Least Square were used to test the relationship between body shape and size, space use and diet, using raw data and phylogenetic independent contrasts. The first two PCs represented 84.7% of all the variation in wing shape of the bats analyzed. PC1 presents a gradient ranging from more large wings on negative portion to narrower wings on the axis positive portion. PC2 presents a gradient from shorter and rounded wings on the axis negative portion and longer wings and triangular tips on positive portion. Wing shape presents a phylogenetic signal (p=0,0641), indicating that the morphology is closely linked to phylogenetic history of the species, but body size does not presented a phylogenetic signal. Ancestral characters reconstruction of wings form demonstrated Vespertilionidae as being closest to common ancestor. Molossidae had their wings narrowed, while in Phyllostomidae were widened compared to the common ancestor. Reconstruction of ancestral characters of size showed that most species maintained the same size pattern of the ancestral in common, with some variations occurring in Vespertilionidae and Phyllostomidae. For the raw data, there was relation of the wing shape with the factors size (p=0,0425), space use (p=0,0391) and diet (p=0,0001), however, there was no relation using data without phylogenetic influence. Bats maintained a base of the ancestral wing's shape throughout the evolution, and this form was little influenced by factors such as size, diet and use of space.